Health reform and its implications - Khalib Abdul Latip,; Nik Shamsidah Nik lbrahim, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
This paper discusses the various types of health reforms, its objectives and principles. Rl&LYtrationsa nd examples of health reforms were given namely dnlg financing health reform, reform in maternal and child health services and health reforms in South Africa, Zambia and Malaysia. Issues in health reforms were also discussed.